Profile of Psoriasis Vulgaris in Waled General Hospital, Cirebon, Indonesia: A Retrospective Study (January 2020-December 2023) - Putra, Fadhlan Adiguna; Rahayu, Frista Martha; Wahdini, Maya (GHMJ (Global Health Management Journal), 2025)
Background: Psoriasis is a chronic skin disease that significantly impacts the quality of life. In Indonesia, it affects 2.5% of the population, with increasing cases observed in major hospitals. This study aimed to profile psoriasis vulgaris at Waled General Hospital, Cirebon, from January 2020 to December 2023. Aims: To understand the profile of psoriasis vulgaris in the Dermatology and Venereology Clinic of Waled General Hospital, Cirebon Regency, for the period January 2020 to December 2023. Methods: This study employed a descriptive, cross-sectional design with a retrospective approach to analyze secondary data sourced from medical records of patients treated at Waled General Hospital. The inclusion criteria focused on individuals diagnosed with psoriasis vulgaris who received treatment or consultation between January 2020 and December 2023, provided their medical records were complete. Conversely, the exclusion criteria removed patients diagnosed with other forms of psoriasis, such as guttate psoriasis, as well as those with incomplete records. The final sample size consisted of 56 patients, ensuring a focused and manageable dataset for analysis. By applying these criteria, the study aimed to provide a clear and accurate understanding of psoriasis vulgaris cases, ensuring the findings were both scientifically robust and clinically relevant. Results: From January 2020 to December 2023, psoriasis vulgaris was most prevalent among the age group of 15-49 years, with a mean age of 42.3 ± 14.7 years comprising 53.57% of the cases. The female sex predominated over the male sex, with 53.57% versus 46.42%. The major clinical presentation in all cases was red plaques, 100%. Hypertension was the most common comorbid condition, affecting 17.85% of the patients. The universal systemic antihistamine used was 100%, while the topical corticosteroid used was performed for 80.35% of the cases. Conclusion: These findings put into perspective the need for early recognition of symptoms, standardized treatment, and integrated care for comorbidities such as hypertension in a regional hospital setting. This study thus provides important lessons that could be used to improve psoriasis management by proactively identifying specific strategies to address demographic and clinical characteristics of affected populations and ultimately improve patient outcomes and resource use.